THE INFLUENCE OF BUSINESS CAPITAL, LABOR COSTS, AND MARKETING COSTS ON THE INCOME OF MSMEs IN SEMBALUN, EAST LOMBOK - Desta Ramdasari; M. Wahyullah (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study aims to determine the effect of business capital, labor, and marketing costs on MSME income inSembalun District, East Lombok Regency. The type of research used is Quantitative research with anAssociative Approach. The sampling technique is a saturated sample, so the population and sample total 185MSMEs. The data analysis method used in this research is multiple linear regression with SPSS 25 statistics:(1) Business capital variable (X1) has an effect on MSME income with a significant value of 0.36 <0.05and a calculated t value of 2.122> 1.980 t table, meaning that the higher the business capital owned byMSMEs, the income received will increase. (2) Labor costs (X2) do not affect MSME revenue as seen fromthe significant value of 0.233> 0.05, and t count 1.200 < 1.980 t table, meaning that the high and lowlabor costs incurred by MSMEs are unable to affect revenue. (3) Marketing costs affect revenue by obtaining asignificant value of 0.003 < 0.05 and a t value of 2.989> 1.980 t table, meaning that the higher themarketing costs incurred, the product will be known to the public so that it will affect the high income receivedby MSMEs